FAMILY HEALTH HISTORY CONFIRMED POSITIVE COVID-19 DURING SELF ISOLATION - Nurliani, Lia; Pragholapati, Andria (Journal of Vocational Nursing, 2022)
Introduction: Coronavirus or the so-called Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-COV2) is a virus variant that was newly discovered in December 2019, in Wuhan China, and is the cause of the infectious disease Coronavirus Disease-2019 (COVID-19). This virus can infect all ages and manifests mild to severe symptoms, and can even cause death. Until now, various efforts have been made to prevent the spread of COVID-19, including the government's policy to self-isolate for people infected with COVID-19 who have mild symptoms. During self-isolation, different health problems may arise for each person. Mental health is very necessary to support physical health during isolation. Method: The method used is a qualitative method, a case study on five family members who were confirmed positive for COVID-19 by describing the health history of each individual. Results: In this study, researchers will use both data analysis techniques, namely quantitatively to synthesize research results with a quantitative approach, for example, Cohort Study or Case-Control Study, Cross Sectional Study, Prospective Study / cohort, Retrospective Study, Rapid Review, Observational Study and qualitatively to synthesize (summarize) the results of the descriptive qualitative research. Conclusions: Isolation independent by someone or group of people with mild COVID-19 symptoms. Isolation independent could walk with good if needs base fulfilled and have good mental health.